(untitled) (Journal of Mining and Metallurgy, Section B: Metallurgy, 2022)
In this study, a high valued product submicronic α-alumina was successfully extracted from aluminum slags generated by the local aluminum industry. The extraction technique was based on the leaching of slags by H2SO4 followed by precipitation. The coarser aluminum-rich fractions of the slags were used in this study instead of the finer oxide-rich fractions that were commonly used in previous studies. The precipitation of the leached slags by NH4OH was controlled by a zetameter in order to determine the optimal precipitation pH. Then, the obtained gel showing the higher precipitation rate and the finer particle size was calcined at 1200 °C and characterized by the XRF, XRD, FTIR, SEM, EDS, and laser granulometry. Even without any pretreatment of slags, the XRF analysis revealed that a high purity and high extraction efficiency of 99.2% and 93.75% respectively could be achieved just at a leaching acid concentration of 15%. The XRD spectrum shows that the produced alumina was pure -corundum, which was confirmed by the FTIR spectrum showing only the Al-O bonds. The laser granulometry showed that the recovered powder exhibited a wide particle size distribution, which was between 50 nm and 20 µm, while the average particle size (d50) was about 400 nm. The SEM observations revealed that the grains were in the form of submicronic whiskers. The above characteristics allowed the obtained alumina powder in this study to be used in the usual applications of alumina such as refractory, ceramic fibers, abrasive, etc. The obtained powders may also assume applications as a thermally stable substitute for the commonly used transition alumina powders, which needs further investigations in future studies.